2007
DOI: 10.1007/s10404-006-0142-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of sorting, aligning, and orienting motile sperm using microfluidic device operated by hydrostatic pressure

Abstract: In vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) are the most commonly used assisted reproductive technologies to overcome male infertility problems. One of the obstacles of IVF and ICSI procedures is separating motile sperm from non-motile sperm to select the most competent sperm population from any given sperm sample. In addition, orientation and separation of the head from the tail is another obstacle for ICSI. Using the self-movement of sperm against flow direction, motile and non-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 20 publications
3
56
0
2
Order By: Relevance
“…However, the red sperms swim upstream against the flow of seminal plasma. The selfmovement of sperm against flow direction has been reported [17]. As to the collapse of the semen drop, the similar wash-away sperms were observed when the voltage was on and we did not observe the sperms swim against the fluidic flow.…”
Section: Resultssupporting
confidence: 81%
“…However, the red sperms swim upstream against the flow of seminal plasma. The selfmovement of sperm against flow direction has been reported [17]. As to the collapse of the semen drop, the similar wash-away sperms were observed when the voltage was on and we did not observe the sperms swim against the fluidic flow.…”
Section: Resultssupporting
confidence: 81%
“…Using our predicted geometries, which, incidentally, were in general agreement with very recent theoretical works [30,31], rows of ∪-shaped obstacles were designed and a high sperm cell concentration was achieved, demonstrating that the interaction of the cells with the rounded walls leads to the rectification and control of the sperm movement without trapping the cells. Our noninvasive procedure is an alternative efficient method to achieve sperm sorting [32,33] and directioning in channels [34] . We have also shown that a characterization of the specific strategy for swimming along walls of each microswimmer species and of its behavior near corners and along edges, together with a knowledge of the motility parameters under 2D confinement will be crucial for designing and modeling efficient biomedical devices.…”
mentioning
confidence: 99%
“…15.7b) All the sperms are then flushed by such a fluidic flow. However, the fertile sperms swim upstream against the fluidic flow because of the nature of the fertile sperms [23]. (Figure 15.7b) When we turn off the voltage, the LC molecules reorientate back along y-direction owing to the elastically essential properties of LC and the anchoring force of polymer grains.…”
Section: Sperm Testing Devices Using Droplet Manipulationmentioning
confidence: 99%